Lola Josa, El arte dramático de Juan Ruiz de Alarcón. Reichenberger, Kassel, 2002; 333 pp. - Ramírez Sierra, Hugo Hernán (El Colegio de México, 2006)
Se reseñó el libro: El arte dramático de Juan Ruiz de Alarcón.